The Effect of Multistage Ammoniation on Fiber Fraction and Digestibility of Maize Stover in vitro - K. Dakaew; A. Abrar; A. Cherdthong (Jurnal Peternakan Sriwijaya, 2016)
The main objective of this experiment was to assess the effect of multistage ammoniation on fiber fraction and digestibility of maize stover in vitro. Maize stover was treated by a multistage technique of different urea connect ration (8%, 4%, and 2%) and incubation for 14 days at room temperature.Digestibility of NDF, ADF, ADL, hemicellulose, and cellulose, in vitro dry matter digestibility (DMD), organic matter digestibility (OMD), NH3-N, total volatile fatty acid (VFA) and pH concentration were observed. However treatment maize stover and multistage ammoniation maize stover were composed by using T-test student as the statistic. There were not significantly different on fiber fraction and digestibility of maize stover. However, multistage ammoniation decreased ADF fraction by 56.67% to45.39%. The DM digestibility of multistage ammoniation on fiber fraction and digestibility of maize stover also increased by 35.18 to 45.91. The total VFA and N-ammonia of multistage ammoniation on fiber fraction and digestibility of maize stover also higher than control.Keywords: Ammoniation, Digestibility, in vitro, Maize stover